What Is the Effect of Using Mobile Augmented Reality in K12 Inquiry-Based Learning? - Margus Pedaste; Geidi Mitt; Teele Jürivete (MDPI AG, 2020)
A systematic review of the potential of implementing augmented reality (AR) in inquiry-based learning was conducted. We considered the purposes, potential advantages, application characteristics and the effects of using AR in inquiry-based learning. The findings reveal that AR, in the context of inquiry-based learning, is mostly implemented successfully to achieve cognitive and, less often, motivational and emotional learning goals. The AR solutions have mainly been applied in the Conceptualization phase and less in the Investigation phase. The affordances of AR in the Orientation, Conclusion and Discussion phases need to be applied in further studies.